2008
DOI: 10.1016/j.metabol.2008.01.036
|View full text |Cite
|
Sign up to set email alerts
|

The role of fatty acids and caveolin-1 in tumor necrosis factor α–induced endothelial cell activation

Abstract: Hypertriglyceridemia and associated high circulating free fatty acids are important risk factors of atherosclerosis. In contrast to omega-3 fatty acids, linoleic acid, the major omega-6 unsaturated fatty acid in the American diet, may be atherogenic by amplifying an endothelial inflammatory response. We hypothesize that omega-6 and omega-3 fatty acids can differentially modulate TNF-α-induced endothelial cell activation and that functional plasma membrane microdomains called caveolae are required for endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 60 publications
4
42
1
3
Order By: Relevance
“…We showed that TNF suppressed claudin-2 expression in cerebral endothelia; however, TNF acts through NF B and increases claudin-2 in HT-29/B6 human colon cells [44]. Nonetheless, the TNF-induced increase of caveolin [48] and decrease of occludin expression in endothelial cells [49] is consistent with our results. We chose the hCMEC/ D3 cell line as a model system since TNF activates NF B in these cells and they express TNF receptors [50,51].…”
Section: Il-15 Activates Nf B Target Genes In Bbb Cellssupporting
confidence: 91%
“…We showed that TNF suppressed claudin-2 expression in cerebral endothelia; however, TNF acts through NF B and increases claudin-2 in HT-29/B6 human colon cells [44]. Nonetheless, the TNF-induced increase of caveolin [48] and decrease of occludin expression in endothelial cells [49] is consistent with our results. We chose the hCMEC/ D3 cell line as a model system since TNF activates NF B in these cells and they express TNF receptors [50,51].…”
Section: Il-15 Activates Nf B Target Genes In Bbb Cellssupporting
confidence: 91%
“…Cav-1 is also slightly upregulated, as reported by other authors using similar diets [22]. This early response of Cav-1 could be related to the high amount of cholesterol and the overload of fatty acids in the diet [22], but also to the release of the inflammatory cytokine TNF-alpha [23]. Therefore, we suggest that, in this prompt response, insulin-related pathways might be activated by a coordinated mechanism mediated by both caveolins and IR, in an attempt to effectively fight against the excess of dietary nutrients in order to maintain glucose balance.…”
Section: Discussionsupporting
confidence: 72%
“…As a result, the anti-inflammatory effects of n-3 PUFA are counteracted by the proinflammatory effects of n-6 PUFA. This hypothesis has been confirmed in a recently published elegant study where endothelial cells in vitro were preexposed to either linoleic acid (n-6 PUFA) or a-linolenic acid (n-3 PUFA) and subsequently exposed to TNF-a [37]. Cells preexposed to linoleic acid (the n-6 PUFA precursor molecule) had an increase of their response to the proinflammatory cytokine TNF-a including induction of p38 mitogen-activated protein kinase (MAPK), NF-kB, COX-2, and PGE2.…”
Section: The N-3 Polyunsaturated Fatty Acids/n-6 Polyunsaturated Fattmentioning
confidence: 67%